2023
DOI: 10.3390/jcm12041469
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Atlanto-Axial Instability: A Combined Clinical and Radiological Approach for the Diagnosis of Pathological Rotational Movement in the Upper Cervical Spine

Abstract: Post-traumatic rotational instability at the atlanto-axial (C1-2) joint is difficult to assess, much less quantify, due to the orientation and motion plane of the joint. Prior investigations have demonstrated that a dynamic axial CT scan, during which the patient maximally rotates the head right and left, can be used to evaluate and quantify the amount of residual overlap between the inferior articulating facet of C1 and the superior facet of C2, as an index of ligamentous laxity at the joint. We have previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The treatment protocols have previously been published in the medical literature and chronic pain conditions have had successive and positive clinical outcomes in short-and long-term studies from single cases to large RCTs. A multi-modal approach to improving spine alignment, abnormal coronal and sagittal balance and posture, as well as improved HRQoLs with CBP® methods has been demonstrated across multiple conditions [8][9][10][29][30][31][32][33][34]. Initial CBP® case studies found that the multiple treatment approach may have been a limitation to the study conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment protocols have previously been published in the medical literature and chronic pain conditions have had successive and positive clinical outcomes in short-and long-term studies from single cases to large RCTs. A multi-modal approach to improving spine alignment, abnormal coronal and sagittal balance and posture, as well as improved HRQoLs with CBP® methods has been demonstrated across multiple conditions [8][9][10][29][30][31][32][33][34]. Initial CBP® case studies found that the multiple treatment approach may have been a limitation to the study conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Initial CBP® case studies found that the multiple treatment approach may have been a limitation to the study conclusions. Recently, growing reports demonstrate that this approach to improving postural muscles, postural non-contractile tissues like disc and ligament, via MI® traction, as well as postural SMT is a repeatable and reliable approach for spine and some extra-spinal conditions [8][9][10][29][30][31][32][33][34]. CWSP and CLBP is such a burden that having the potential of the safe, efficacious, and repeatable methods of CBP® to reduce GBD is desirable for astute clinicians who treat spine pain and extremely beneficial with low potential for poor outcomes for the patient [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of the writing of this Editorial, there were 15 unique manuscripts accepted for publication in the Special Issue: Spine Rehabilitation in 2022 and Beyond. These manuscripts include the following categories of articles: a cross-sectional survey comparing two distinct quality of life questionnaires in adults with scoliosis [46]; a retrospective consecutive cohort investigation examining the relationship of vertebral y-axis rotation of the lumbar spine in functional scoliosis with leg length inequality to sacral shelf lateral tilt angles [47]; a profession wide survey of the chiropractic profession regarding spine radiography utilization examining clinical opinions and experience [48]; a novel clinical manual method comparing manual palpation and motion vs. diagnostic imaging to determine pathological rotational instability movement of the upper cervical spine [49]; four case-control investigations seeking to identify any correlations between spine and posture displacements and patient pain, disability, neurophysiology, and sensory-motor control variables [50][51][52][53]; one case series looking at the relationship between non-surgical sagittal plane cervical spine correction and the improvement in upper cervical spine rotational instability [54]; five randomized trials examining the relationship between correction/reduction of cervical and thoracic posture deformities and spine displacements and improvements of a variety of clinical outcome measures including pain, disability, neurophysiology, range of motion, and sensory-motor control measures [55][56][57][58][59]; and, lastly, one systematic literature review that sought to understand the differences in low back pain and disability characteristics in adults with and without scoliotic spine deformities [60].…”
Section: Special Issue Main Accepted Articlesmentioning
confidence: 99%
“…Importantly, each one of these 15 accepted manuscripts offers unique and succinct relevant data that provide further evidence that the 'bio' (biology and biomechanics) component of the 'bio-psycho-social' model of spine care is extremely important to understanding patient pain, disability, and dysfunction and to providing enhanced treatment procedures that improve the outcomes of patient care [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. As such, this Special Issue on spine rehabilitation provides useful, cutting-edge, relevant information that should prove to be useful to improve patient care and outcomes in populations suffering from a wide variety of spine related disorders.…”
Section: Special Issue Main Accepted Articlesmentioning
confidence: 99%
See 1 more Smart Citation